Analisis Hubungan Lebar Karapas dan Berat Rajungan (Portunus pelagicus) di Desa Aengdake Kabupaten Sumenep, Jawa Timur, Indonesia - Khalifatul Khair; Zainul Hidayah; Akhmad Farid (Samakia : Jurnal Ilmu Perikanan, 2024)
Blue swimming crab (Portunus Pelagicus) is a type of marine animal that has quite high economic value, so it is quite attractive to the surrounding community, especially the people in Sumenep Regency. The aim of this study was to find out the growth pattern of variations in carapace width and weight of blue swimming crab (Portunus Pelagicus) in the waters of the southern part of Sumenep Regency. This research was conducted in May 2023 in the village of Aengdake Sumenep. Retrieval of blue swimming crab data includes calculating the width of the carapace and the weight of the crab. The maximum width of the crab carapace is 16 cm while the maximum weight of the crab is 164 grams. From the calculation data for the width-weight relationship, it can be seen that the value of b is 0.74 where this value indicates that the growth pattern of blue swimming crab in the waters of Aengdake Village, Sumenep Regency with a sample of 100 crabs, shows a negative allometric growth pattern. So it is known that the growth in width is faster than the growth in weight.